High field metabolic rates of wild harbour porpoises - Rojano-Doñate, Laia; McDonald, Birgitte I.; Wisniewska, Danuta M.; Johnson, Mark; Teilmann, Jonas; Wahlberg, Magnus; Højer-Kristensen, Jakob; Madsen, Peter T. (Journal of Experimental Biology, 2019)
This study was partly funded by the German Federal Agency for Nature Conservation (BfN) under the project ‘Under Water Experiments’ (project number FKZ 3515822000) and the BfN Cluster 7 ‘Effects of underwater noise on marine vertebrates’ (Z1.2-53302/2010/14) with additional support to P.T.M. and L.R.-D. from the Danish National Research Foundation (FNU) and the Carlsberg Foundation. B.I.M. was supported by a National Science Foundation International Research Postdoctoral Fellowship (OISE – 1150123). M.J. was supported by the Marine Alliance for Science and Technology Scotland (MASTS) and by a Marie Skłodowska-Curie award. Reliable estimates of field metabolic rates (FMRs) in wild animals are essential for quantifying their ecological roles, as well as for evaluating fitness consequences of anthropogenic disturbances. Yet, standard methods for measuring FMR are difficult to use on free-ranging cetaceans whose FMR may deviate substantially from scaling predictions using terrestrial mammals. Harbour porpoises (Phocoena phocoena) are among the smallest marine mammals, and yet they live in cold, high-latitude waters where their high surface-to-volume ratio suggests high FMRs to stay warm. However, published FMR estimates of harbour porpoises are contradictory, with some studies claiming high FMRs and others concluding that the energetic requirements of porpoises resemble those of similar-sized terrestrial mammals. Here, we address this controversy using data from a combination of captive and wild porpoises to estimate the FMR of wild porpoises. We show that FMRs of harbour porpoises are up to two times greater than for similar-sized terrestrial mammals, supporting the hypothesis that small, carnivorous marine mammals in cold water have elevated FMRs. Despite the potential cost of thermoregulation in colder water, harbour porpoise FMRs are stable over seasonally changing water temperatures. Varying heat loss seems to be managed via cyclical fluctuations in energy intake, which serve to build up a blubber layer that ...